1991
DOI: 10.1002/prop.2190390502
|View full text |Cite
|
Sign up to set email alerts
|

Hadronic Production of Charm Particles

Abstract: Charm hadron production is reviewed from the view‐point of an experimentalist. Results are presented on total cross‐section measurements for charm‐anticharm pairs, on its dependence on the atomic number as well as results on xF and p⊥2 behaviour of charm particles produced in hadronic interactions. Correlation studies and charm hadron spectroscopy are also included in this review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
1998
1998

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The comprehensive reviews of the current experimental status of the charm production problem can be found in Ref. [100].…”
Section: Charm Production and Prompt Muonsmentioning
confidence: 99%
“…The comprehensive reviews of the current experimental status of the charm production problem can be found in Ref. [100].…”
Section: Charm Production and Prompt Muonsmentioning
confidence: 99%